Limited Feedback Multiuser MIMO Techniques for Time-Correlated Channels. (2nd September 2009) - Zacarías B Zacarías B, Eduardo Eduardo; Werner Werner, Stefan Stefan; Wichman Wichman, Risto Risto
Abstract : This work presents limited feedback schemes for closed-loop multiple-input multiple-output systems using frequency division duplex. The proposed methods employ compact feedback messages in order to (a) feed back and track a complete frequency-flat channel matrix, to be used as input to multiuser multiplexing methods designed for full channel side information (CSI) at the transmitter, and (b) enable the receiver to command the transmit weight adaptation, in order to maximize the link reliability under strong intercell interference. Simulations show that the channel feedback accuracy provided by the proposed algorithms produces a negligible bit error probability (BEP) performance loss in low mobility scenarios compared to the full CSI performance, and that the proposed interference rejection techniques can effectively exploit an estimate of the interference statistics in order to enable multiple-stream communications under the permanent presence of intercell interference signals.